Polluted promises : environmental racism and the search for justice in a southern town - Checker, Melissa (New York University Press, 2005)
Association for Humanist Sociology 2007 Book Award co-winnerJulian Steward Award 2006 Runner-UpOver the past two decades, environmental racism has become the rallying cry for many communities as they discover the contaminations of toxic chemicals and industrial waste in their own backyards.Living next door to factories and industrial sites for years, the people in these communities often have record health problems and debilitating medical conditions. Melissa Checker tells the story of one such neighborhood, Hyde Park, in Augusta, Georgia, and the tenacious activism of its two hundred African American families. This community, at one time surrounded by nine polluting industries, is struggling to make their voices heard and their community safe again. Polluted Promises shows that even in the post-civil rights era, race and class are still key factors in determining the politics of pollution.